2016
DOI: 10.1155/2016/9605253
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α-Dependent Mitochondrial Adaptation Is Necessary to Sustain IL-2-Induced Activities in Human NK Cells

Abstract: Human Natural Killer (NK) cells are a specialized heterogeneous subpopulation of lymphocytes involved in antitumor defense reactions. NK cell effector functions are critically dependent on cytokines and metabolic activity. Among various cytokines modulating NK cell function, interleukin-2 (IL-2) can induce a more potent cytotoxic activity defined as lymphokine activated killer activity (LAK). Our aim was to determine if IL-2 induces changes at the mitochondrial level in NK cells to support the bioenergetic dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…The metabolism of NK cell is highly dependent on mTORC1, a complex functioning as a nutrient and metabolic sensor and coordinating protein synthesis [39]. The mTORC1 activity of NK cells were shown to elevate upon cytokine stimulation, promoting glycolytic flux enhancement [26,27,59]. Our data demonstrated that NK cells from HSP patients possessed a lower mTORC1 activity than that from healthy children upon cytokine stimulation, in line with the decreased NK cell glycolysis rate in HSP patients based on our study.…”
Section: Discussionsupporting
confidence: 83%
“…The metabolism of NK cell is highly dependent on mTORC1, a complex functioning as a nutrient and metabolic sensor and coordinating protein synthesis [39]. The mTORC1 activity of NK cells were shown to elevate upon cytokine stimulation, promoting glycolytic flux enhancement [26,27,59]. Our data demonstrated that NK cells from HSP patients possessed a lower mTORC1 activity than that from healthy children upon cytokine stimulation, in line with the decreased NK cell glycolysis rate in HSP patients based on our study.…”
Section: Discussionsupporting
confidence: 83%
“…However, there is evidence for roles in tumor-immune cell interactions; for example, PGC-1β has an important function in M2 macrophages, the macrophage population that promotes tumor escape and progression [60]. Furthermore, activation of cytolytic immune cells, such as natural killer (NK) cells or CD8+ T-cell subsets seems to rely on glycolysis [61, 62]; however, recent studies indicate a pivotal role for PGC-1α and oxidative metabolism in proper functions of NK cells and tumor-infiltrating T cells [63, 64], suggesting the multiple facets of PGC-1 functions within tumor niches. Understanding the involvement of PGC-1 coactivators between tumor and immune cells will be instrumental to help improve cancer immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…At the mitochondrial level, cytokine stimulation can also induce significant changes. Miranda et al looked at IL2 induced mitochondrial changes in human NK cells (21). They showed that IL2 stimulation increased both the mitochondrial mass and the mitochondrial membrane potential.…”
Section: Nk Cell Metabolismmentioning
confidence: 99%
“…In this study, TGFβ signaling via the canonical pathway culminated in the upregulation of PGC-1α expression. Interestingly, PGC-1α mediated increases in mitochondrial mass and polarization has been shown to be essential for NK cell IFNγ production (21).…”
Section: Tgfβ and Mitochondrial Structure And Functionmentioning
confidence: 99%